Sistem Membuka Pintu Dengan Ketukan Bernada Menggunakan Mikrokontroler Atmega328 - Ahmad, Adi; Ikhlas, Muhammad (STIKOM Tunas Bangsa Pematangsiantar, 2020)
Door keys are susceptible to the risk of being left behind or lost. Nowadays, the security system is the most important in our daily life. It requires protection or security to save it. This research is designed to build home doors security by using a knock pattern. The process is by doing knock on it, identification until the verification of each knock pattern is recognized. Along with the development of technologies are increasingly fast and try to answer all of the human needs. The system will start working by doing the accuracy of the interval between beats; when the rhythm/rhythm knock based on the previous data stored, then the system is active. Thus, the authors tried to develop a tool that is used as a key to the door home by way of knocking on the door with the rhythm/rhythm, which has been adjusted by a knock. Using this tool it is expected to help and maintain home security in a better way.